2000
DOI: 10.1159/000041027
|View full text |Cite
|
Sign up to set email alerts
|

Type I and Type II T Cell Profiles in Chronic Myelogenous Leukemia

Abstract: T cell immunity is considered to play an important role in the control of cell growth in chronic myelogenous leukemia (CML) although information regarding the characteristics of T lymphocytes in CML patients is limited. Using flow cytometric analysis of intracellular cytokine expression at the single-cell level, we analyzed helper T and cytotoxic T subsets in 8 CML patients. The percentage of interferon-γ (IFN-γ) single-positive CD4 cells (Th1) and that of interleukin-4 (IL-4) single-positive CD4 cells (Th2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
0
7
1
Order By: Relevance
“…IM inhibits activation and proliferation of CD4 T lymphocytes in vitro, suppresses CD4 T cell cytokine secretion, and modulates a shift toward a Th2 response (15,19,74). In addition, because IM influences Ag-presenting functions of dendritic cells, the effect of IM on APCs may compromise CD4 Th activity as well as have a direct effect on CD8 T cell function (10,75,76).…”
Section: Discussionmentioning
confidence: 99%
“…IM inhibits activation and proliferation of CD4 T lymphocytes in vitro, suppresses CD4 T cell cytokine secretion, and modulates a shift toward a Th2 response (15,19,74). In addition, because IM influences Ag-presenting functions of dendritic cells, the effect of IM on APCs may compromise CD4 Th activity as well as have a direct effect on CD8 T cell function (10,75,76).…”
Section: Discussionmentioning
confidence: 99%
“…Cell number and cytokine secretion in AML N Panoskaltsis et al (CML), 17,18,28 studies in AML have been lacking. The extent and type of cytokine activity shown in the present work in patients with untreated AML were unexpected (Figures 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic and functional abnormalities of the immune system of CML patients have been well described (Spiers et al , 1977; Dowding et al , 1984; Tsuda & Yamasaki, 2000). Several reports have suggested that NK cells decrease in number and function during the course of CML, and are restored in accordance with a reduction in white blood cell counts (Pierson & Miller, 1996; Guarini et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive examination of the T‐cell compartments in CML patients has shown increased T‐cell numbers before treatment (Spiers et al , 1977) due to balanced expansion of helper and suppressor cells (Dowding et al , 1984), or increased anergic T lymphocytes (Tsuda & Yamasaki, 2000). In contrast, a marked decline in CD8 lymphocytes, compared with CD4 lymphocytes, has been reported at diagnosis but not at the stage of complete remission (Guarini et al, 2001).…”
mentioning
confidence: 99%